Multivariate relationships between morphology, movement patterns and speed abilities in elite young, male athletes - Kozlenia, D.; Domaradzki, J.; Trojanowska , I. (Kinesiologia Slovenica, 2020)
Speed and agility are crucial abilities in many team sports such as soccer, basketball or handball. Therefore determing factors affect speed abilities is relevant. To investigate multidimensional correlations of the FMS test results with speed abilities. 35 male team sport players, aged 21.31±0.93. Body weight and body height were measured and BMI was calculated (kg/m2). Three modules of the FMS test were used to analyse: Deep Squat, Hurdle Step, In-line Lunge. Linear speed was measured based on the 20m Linear Speed test, agility was evaluated using the Agility T-test. Data were analysed by Canonical Correlation Analysis (CAA). The CCA analysis demonstrated statistically significant correlation between morphological features and agility. Correlation was found between 20m Linear Speed and In-line Lunge. However it was not revealed any significant correlations of neither speed skills nor morphological characteristics with chosen FMS subtests. High canonical loadings and weights suggested the presence of correlations (not significant) between individual measurements. The correlations between morphological measurements and functional movement were very close to statistical significance. The CCA analysis allowed for showing multivariate links between morphological features and functional abilities. This results demonstrated moderate correlations between body morphology and agility and between movement patterns and agility. Better scores in agility were correlated with good performance in In-line Lunge and Hurdle Step test.